Coordination of Phospholipid-Based Signaling and Membrane Trafficking in Plant Immunity. (April 2021) - Xing, Jingjing; Zhang, Liang; Duan, Zhikun; Lin, Jinxing
Abstract : In plants, defense-associated signal transduction involves key membrane-related processes, such as phospholipid-based signaling and membrane trafficking. Coordination of these processes occurs in the lipid bilayer of plasma membrane (PM) and luminal/extracellular membranes. Deciphering the spatiotemporal organization of phospholipids and lipid–protein interactions provides crucial information on the mechanisms that link phospholipid-based signaling and membrane trafficking in plant immunity. In this review, we summarize recent advances in our understanding of these connections, including deployment of key enzymes and molecules in phospholipid pathways, and roles of lipid diversity in membrane trafficking. We highlight the mechanisms that mediate feedback between phospholipid-based signaling and membrane trafficking to regulate plant immunity, including their novel roles in balancing endocytosis and exocytosis. Highlights: Coordination of phospholipid-based signaling and membrane trafficking connects perception of pathogens with the activation of efficient defense reactions in plant immunity. Exploring the spatiotemporal organization of phospholipids and lipid–protein interactions provides crucial information for elucidating this coordination. The functions of phospholipids and their derivatives include: acting as lipid landmarks of various membranes; promoting membrane deformation; regulating cytoskeletal dynamics; and recruiting trafficking regulators. Phospholipid-derived molecules have crucial roles in regulating endocytosis, exocytosis, and the exo/endocytosis balance. During biotic stress, feedback between phospholipid-based signaling and membrane trafficking coordinates signal recognition and activation of immune responses.